Polymer composition curable at room temperature and made from polyaldehydes and polymalonates

By using two-component polymers containing aldehyde and malonate groups and combining with non-metal catalysts, the toxicity, moisture sensitivity and bubble formation problems of the polymer system in the prior art are solved, and high strength and high quality are achieved Stressability and good hot water stability, suitable for a variety of application scenarios.

CN119301168APending Publication Date: 2025-01-10SIKA TECH AG
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380046302.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-13
Filing Date
2023-06-21
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing room temperature curable polymer system has problems such as toxicity, moisture sensitivity and bubble formation during use, resulting in incomplete curing, loss of strength and elasticity, and the catalyst is sensitive to environmental humidity, affecting stability and application range.

Method used

Using two-component polymers containing aldehyde and malonate groups, rapid and defect-free curing is achieved through non-metallic catalysts such as tertiary amines, to form a non-viscosity polymer with high ductility and high strength, avoiding Moisture and bubble formation, suitable for applications between thick layers and waterproof substrates.

Benefits of technology

Achieve high strength, high ductility and good hot water stability, simplify the processing process, reduce dependence on solvents and water, improve storage and application stability and safety, and is suitable for a variety of environmental and mechanical stresses Use under.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The present application relates to a curable composition comprising:-a first component comprising an aldehyde group-containing compound comprising at least one compound having two or more aldehyde groups, and-a second component comprising a malonate group-containing compound comprising at least one compound having two or more malonate groups of formula (I), wherein the average molecular weight Mn of at least one of the two components associated with the compound containing an aldehyde group or malonate group is in the range of 400 to 20000 g / mol. The composition is substantially free of toxicologically hazardous components and can cure quickly and without defects into non-tacky elastomeric polymers under ambient conditions using conventional catalysts, which have very high strength and ductility. The present invention relates to polyurethane elastomer compositions which are particularly suitable for use as elastic adhesives, sealants or coatings, which have very high robustness in production, storage and processing and very high resistance after curing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a two-component composition and its use as room temperature curable elastic adhesive, sealant or coating.

[0002] Prior art

[0003] Reactive polymer compositions that are curable at room temperature and can be used as elastic adhesives, sealants or coatings are known. Polyurethane systems that cure and form particularly highly elastic polymers by reaction of isocyanate groups with polyols and / or moisture are widely used. The preparation, production and use of polyurethane systems constitute a series of challenges in practice. They usually contain a large amount of monomeric diisocyanates, which can irritate the eyes, skin and mucous membranes. The moisture sensitivity of the isocyanate groups can lead to premature crosslinking reactions associated with increased viscosity until gel, and thus affect the shelf life or storage stability. In the case of systems formulated in a one-component form, the water required for curing must penetrate from the outside in the form of air moisture, which makes it difficult to use in thick layers or between moisture-proof substrates. In the case of a two-component system with a polyol component and an isocyanate component, the problem is that the isocyanate groups can react not only with the hydroxyl groups of the polyol, but also with any water that may be present. In particular, in the case of high ambient humidity, this can trigger bubble formation and cause incomplete polymerization of chain termination due to only partially bound polyols, which leads to a more or less loss of strength and elasticity. These problems hardly occur when using mercury catalysts, which catalyze the reaction with polyols very selectively. However, mercury catalysts have not been available for a long time due to their high toxicity. As an alternative, two-component polyurethanes are usually catalyzed with tin compounds and / or tertiary amines, but their selectivity is significantly lower, so that bubbles may form, especially at high ambient humidity. Bismuth catalysts or zirconium catalysts have a higher selectivity; however, these and other alternative metal catalysts are sensitive to hydrolysis, so that the catalytic activity is greatly lost, which in turn can lead to curing defects.

[0004] Also widely used are reactive polymer compositions based on silane-functional polymers (SMP / STP) and silicones. These polymer systems cure by hydrolysis and condensation of the silane groups, releasing alcohols, especially methanol or ethanol, or oximes, which are toxic and cause VOC emissions; in addition, they usually contain large amounts of low molecular weight silanes as crosslinkers or drying agents, which are likewise harmful to health. Due to the moisture sensitivity of the silane groups, these polymer systems are also demanding in terms of production and use and do not always produce the desired results.

[0005] Also known are water-based polymer systems, which are usually based on acrylate dispersions or polyurethane dispersions. These cure by evaporation and coalescence of water and are essentially free of chemically reactive groups. However, they can only be used in relatively thin layers and only between open-pored substrates, the rate of curing is highly dependent on the ambient humidity, and they have high shrinkage. After curing, due to the included surfactants required for dispersion production and stability, water sensitivity increases, which can lead to reduced durability, especially in outdoor applications.

[0006] US 2018 / 0282477 describes the use of polyesters containing malonate groups for crosslinking compounds with activated C=C double bonds, such as acrylates or methacrylates in particular. By using specific catalysts, this results in coatings with high hardness and virtually no elasticity. SUMMARY OF THE INVENTION

[0007] It was therefore an object of the present invention to provide novel polymer compositions which are curable at room temperature and are suitable as elastic adhesives, sealants or coatings and which overcome the disadvantages of the known polymer systems.

[0008] Surprisingly, this object is achieved by a curable composition according to claim 1. The composition comprises a first component containing a compound containing aldehyde groups and a second component containing a compound containing malonate groups, wherein the average molecular weight M of at least one of the two components related to the compound containing aldehyde groups or malonate groups is n The composition has several advantageous and surprising properties compared to room temperature curable polymer systems according to the prior art.

[0009] Both the compounds containing aldehyde groups and the compounds containing malonate groups are substances of very low toxicological concern, which do not require hazard marking and can be handled without special precautions. The composition according to the invention is insensitive to moisture and bubble formation and enables a high degree of freedom in formulation, since additives commonly used in curable compositions can be used in both components without causing storage stability problems for the respective components. Surprisingly, the composition is very tolerant of the stoichiometric ratio of the reactive groups and in each case, over the entire range of the ratio of the number of malonate groups to the number of aldehyde groups from 1 to 2 or more, a cured non-stick material with high ductility and strength and good stability to heat and water is formed. This is very surprising, since reactive systems according to the prior art generally show a significant reduction in mechanical quality in the case of large deviations from the optimal stoichiometry of the reactive groups (usually close to 1:1). For these reasons, the mixing ratio of the two components can be adjusted almost as desired, which allows a great degree of freedom in the application method and a simple, very reliable processing with high fault tolerance. The composition has good processability under ambient conditions, does not require organic solvents for dissolving or diluting or water for emulsifying or dispersing the composition. The composition cures surprisingly quickly and flawlessly under ambient conditions, regardless of humidity and without causing emissions. It is particularly advantageous that the curing rate is very effectively controlled with conventional catalysts, especially non-metallic bases such as tertiary amines, amidines or guanidines. A high-strength and high-ductility non-viscous elastic polymer is formed by curing, which has good tear strength and stability to heat and water. Due to the combination of these favorable properties, the composition of the present invention has particularly simple handling and no special protective measures, high robustness (Robustheit) and long life in the production and storage of components, in its use under a wide range of environmental and application conditions and mixing ratio fluctuations, and after curing under mechanical, thermal or chemical stress.

[0010] The compositions of the invention are therefore very suitable for use as high-quality elastic adhesives, sealants or coatings.

[0011] Further aspects of the invention are the subject matter of further independent claims. Particularly preferred embodiments of the invention are the subject matter of the dependent claims. DETAILED DESCRIPTION

[0012] The present invention provides a curable composition comprising:

[0013] - a first component containing an aldehyde group-containing compound, which comprises at least one compound having two or more aldehyde groups, and

[0014] a second component containing malonate group-containing compounds, which comprises at least one compound having two or more malonate groups of formula (I),

[0015] The average molecular weight Mn of at least one of the two components related to the compound containing aldehyde groups or malonate groups is in the range from 400 to 20,000 g / mol.

[0016] "Aldehyde" refers to the formula functional groups.

[0017] The dashed lines in the formulae here represent in each case the bond between a substituent and the remainder of the molecule to which it belongs.

[0018] "Molecular weight" refers to the molar mass of a molecule (g / mol). "Average molecular weight" refers to the number average molecular weight (Mn) of a polydisperse mixture of oligomeric or polymeric molecules. It is determined by gel permeation chromatography (GPC) using polystyrene as a standard.

[0019] A "storage-stable" composition is one that can be stored in a suitable container at room temperature for an extended period of time, typically at least 3 months to 6 months or more, without such storage resulting in a change in its application or use properties to an extent relevant to its use.

[0020] Substance names beginning with "poly", such as polymalonate, polyaldehyde or polyol, refer to substances which formally contain two or more of the functional groups appearing in their names per molecule.

[0021] "Room temperature" refers to a temperature of 23°C.

[0022] All industry standards and specifications mentioned in this document refer to the versions in effect on the date of initial submission.

[0023] Unless otherwise indicated, weight percent (% wt) refers to the mass proportion of a component of a composition or molecule, based on the entire composition or the entire molecule. The terms "mass" and "weight" are used synonymously herein.

[0024] The first and second components of the curable composition are themselves storage-stable and are stored in separate containers until they are mixed with one another shortly before or during application.

[0025] In the curable composition, at least one of the two components related to the compound containing aldehyde groups or malonate groups has an average molecular weight Mn of 400-20000 g / mol. Such a composition cures to give a high-strength elastic polymer.

[0026] Preferably, at least one of the two components associated with the compound containing aldehyde groups or containing malonate groups has an average molecular weight Mn in the range of 1000 g / mol to 20000 g / mol, preferably 1500 g / mol to 15000 g / mol, in particular 2000 g / mol to 10000 g / mol. This enables particularly high ductility to be achieved.

[0027] The compound having two or more aldehyde groups is preferably liquid at room temperature. In particular, its viscosity at 20° C. is 0.2-700 Pa·s, preferably 0.3-500 Pa·s, more preferably 0.5-200 Pa·s, and especially 1-100 Pa·s, and the viscosity is 0.2-700 Pa·s, preferably 0.3-500 Pa·s, more preferably 0.5-200 Pa·s, and especially 1-100 Pa·s, by a cone diameter of 10 mm, a cone angle of 1°, a cone tip-plate distance of 0.05 mm, a shear rate of 10 s -1 The viscosity can be measured with a cone and plate viscometer and is less than 1 Pa·s using a cone diameter of 50 mm. These compounds can be easily processed at ambient temperature even without the addition of solvents or diluents.

[0028] Preferred compounds having two or more aldehyde groups are polymers having aldehyde groups.

[0029] Preferably, the average molecular weight M of the first component associated with the aldehyde-containing compound is n 1000-20000 g / mol, preferably 1500-15000 g / mol, especially 2000-10000 g / mol, measured by gel permeation chromatography (GPC) with polystyrene as standard. Even without adding solvents or diluents, this component is easy to process at ambient temperature and gives the polymer high ductility and elasticity.

[0030] Preferably, the average aldehyde functionality of the aldehyde-containing compound is 1.6-4, preferably 1.8-3.5, more preferably 2.0-3.0, especially 2.2-3.0. This allows the cured composition to have high ductility, strength and stability.

[0031] The compound containing an aldehyde group preferably comprises a polymer having a polymer backbone containing poly(oxyalkylene) units and / or polyester units.

[0032] Preferred poly(oxyalkylene)s are poly(oxyethylene), poly(oxy-1,2-propylene), poly(oxy-1,3-propylene), poly(oxy-1,4-butylene), poly(oxy-1,2-butylene) or mixed forms of these poly(oxyalkylene). Among them, poly(oxy-1,2-propylene), poly(oxy-1,3-propylene) or poly(oxy-1,4-butylene), especially poly(oxy-1,2-propylene), the latter of which may contain 0 to 25% by weight of poly(oxyethylene) units, based on the poly(oxyalkylene) backbone, especially at the chain ends. Aldehyde-functional polymers with such backbones have low viscosity and can therefore be processed particularly efficiently and are particularly hydrophobic. They give compositions having particularly good processability, high ductility and good water resistance.

[0033] Preferred polyesters are esters of dicarboxylic acids and diols or triols, triglycerides or polyesters based on dimerized or trimerized fatty acids. Particularly preferred are polyesters of dimerized fatty acids or polyesters derived from castor oil, castor oil or vegetable oil derivatives. Aldehyde-functional polymers with such backbones are particularly hydrophobic and impart particularly high heat and water resistance to the composition. They are also based on renewable raw materials and are therefore particularly sustainable.

[0034] The compounds having two or more aldehyde groups preferably additionally contain urethane groups. This results in a composition having particularly high ductility.

[0035] Preferably, the compound containing aldehyde groups comprises a polymer containing urethane groups, which is liquid at room temperature and has an average molecular weight M of 1000 to 20000 g / mol, preferably 1500 to 15000 g / mol, in particular 2000 to 10000 g / mol. n , and an average aldehyde functionality of 1.8 to 3.5, more preferably 2.0 to 3.0, especially 2.2 to 3.0.

[0036] Preferably, the compound having two or more aldehyde groups is obtained from the reaction of at least one hydroxyaldehyde with at least one polymer containing isocyanate groups or at least one polyisocyanate.

[0037] Suitable hydroxyaldehydes are, in particular, compounds having a molecular weight of 60 to 500 g / mol, preferably 60 to 250 g / mol.

[0038] The following are particularly suitable: 2-hydroxyacetaldehyde, 3-hydroxybutyraldehyde, 3-hydroxypivalaldehyde, 5-hydroxyvaleraldehyde, 2-(2-hydroxyethoxy)acetaldehyde, 3-(2-hydroxyethoxy)propionaldehyde, 5-hydroxymethylfurfural, alkoxylated o-, m- or p-hydroxybenzaldehyde or alkoxylated vanillin, where "alkoxylated" preferably means (mono- or poly-) "ethoxylated" or "propoxylated", and 4,4'-(2-hydroxypropane-1,3-diyl)bis(oxy)bis(benzaldehyde) or 4,4'-(2-hydroxypropane-1,3-diyl)bis(oxy)bis(3-methoxybenzaldehyde).

[0039] Preference is given to ethoxylated salicylaldehydes, especially 2-(2-hydroxyethoxy)benzaldehyde, ethoxylated vanillins, especially 4-(2-hydroxyethoxy)-3-methoxybenzaldehyde, 5-hydroxymethylfurfural, N'-2-hydroxyethyl-N-piperazinyl-2,2-dimethylpropanal or N'-3-hydroxypropyl-N-piperazinyl-2,2-dimethylpropanal. These hydroxyaldehydes are obtainable in a simple manner and impart low viscosity and thus good processability to the aldehyde-containing compounds, as well as good processability and high strength and ductility to the compositions.

[0040] A particularly preferred hydroxyaldehyde is 5-hydroxymethylfurfural. This hydroxyaldehyde is obtainable from renewable raw materials and surprisingly enables particularly low-viscosity compounds with aldehyde groups and curable compositions having particularly good processability and high strength, ductility and heat and water resistance to be obtained.

[0041] Suitable polymers containing isocyanate groups for preparing compounds having two or more aldehyde groups are, in particular, reaction products of polyols with diisocyanates, in particular in an NCO / OH molar ratio of 1.5 / 1 to 10 / 1, wherein unconverted monomeric diisocyanates are optionally removed from the polymer.

[0042] The isocyanate group-containing polymer preferably has a content of free isocyanate groups of 0.5 to 15% by weight, more preferably 1 to 10% by weight, in particular 1.5 to 6% by weight, based on the isocyanate group-containing polymer.

[0043] Very particularly preferred polymers containing isocyanate groups are reaction products from the reaction of at least one diisocyanate and at least one polyol in an NCO / OH ratio of at least 3 / 1, preferably from 3 / 1 to 10 / 1, in particular from 4 / 1 to 8 / 1, and subsequent removal of the majority of the monomeric diisocyanate by suitable separation methods, so that the polymer containing isocyanate groups ultimately has a monomeric diisocyanate content of not more than 0.2% by weight, based on the polymer containing isocyanate groups.

[0044] Such polymers containing isocyanate groups allow aldehyde-functional polymers to have a particularly low content of reaction products from monomeric diisocyanates and hydroxyaldehydes, in particular a content of these reaction products of less than 0.5% by weight, based on the aldehyde-functional polymer. This results in curable compositions having particularly simple processing, long open times and rapid curing as well as particularly good flexibility.

[0045] Suitable diisocyanates are, in particular, hexane 1,6-diisocyanate (HDI), 2,2(4),4-trimethylhexane-1,6-diisocyanate (TMDI), 1-methyl-2,4(6)-diisocyanatocyclohexane (H6TDI), isophorone diisocyanate (IPDI), 4,4'-diisocyanatodicyclohexylmethane (H 12 MDI), 4(2),4'-diphenylmethane diisocyanate (MDI) or 2,4(6)-toluene diisocyanate. HDI, IPDI, TDI or MDI are preferred. IPDI is particularly preferred. This provides a composition with particularly good processability, which cures to give a polymer with high strength and ductility.

[0046] Suitable polyols are especially

[0047] - polyether polyols, in particular polyoxyalkylene diols or polyoxyalkylene triols, in particular the polymerization products of ethylene oxide or 1,2-propylene oxide or 1,2- or 2,3-butylene oxide or oxetane or tetrahydrofuran or mixtures thereof, where these can be polymerized with the aid of starter molecules having two or more active hydrogen atoms, in particular starter molecules such as water, ammonia or compounds having a plurality of OH or NH groups, for example 1,2-ethylene glycol , 1,2- or -1,3-propylene glycol, neopentyl glycol, diethylene glycol, triethylene glycol, isomeric dipropylene glycol or tripropylene glycol, isomeric butanediols, pentanediol, hexanediol, heptanediol, octanediol, nonanediol, decanediol, undecanediol, 1,3- or -1,4-cyclohexanedimethanol, bisphenol A, hydrogenated bisphenol A, 1,1,1-trimethylolethane, 1,1,1-trimethylolpropane, glycerol or aniline, or a mixture of the above compounds.

[0048] Preferred polyether polyols are polyoxypropylene diols or polyoxypropylene triols, or so-called ethylene oxide-terminated (EO-terminated or EO-terminated) polyoxypropylene diols or triols. The latter are polyoxypropylene-polyoxyethylene mixed polyols, which are obtained, in particular, by further alkoxylating polyoxypropylene diols or triols with ethylene oxide after the propoxylation reaction is complete, whereby they ultimately have primary hydroxyl groups.

[0049] Preferred polyether polyols have an unsaturation of less than 0.02 mEq / g, especially less than 0.01 mEq / g.

[0050] - Polyester polyols, in particular those obtained from the polycondensation of hydroxycarboxylic acids or lactones or of aliphatic and / or aromatic polycarboxylic acids with diols or polyols. Preference is given to amorphous dimerized or trimerized fatty acid-based polyester polyols, such as are commercially available from Croda.

[0051] - Polycarbonate polyols, obtainable, for example, by reaction of diols with dialkyl carbonates, diaryl carbonates or phosgene.

[0052] - Block copolymers with at least two hydroxyl groups, especially polyether polyester polyols.

[0053] – Polyacrylate polyols and polymethacrylate polyols.

[0054] - polyhydroxy-functional fats or oils, in particular natural fats or oils, such as, in particular, castor oil, castor oil derivatives; or so-called oleochemical polyols obtained by chemical modification of natural fats and oils, such as those available under the trade name Sovermol ® Hydroxylated vegetable oils obtained from BASF.

[0055] - Polyolefin polyols, such as, in particular, polyhydroxy-functional polyolefins, polyisobutylene, polyisoprene; polyhydroxy-functional ethylene / propylene, ethylene / butylene or ethylene / propylene / diene copolymers, such as those produced, for example, by Kraton Polymers; polyhydroxy-functional polymers of dienes, in particular 1,3-butadiene, which can also be prepared, in particular, by anionic polymerization; polyhydroxy-functional copolymers of dienes, such as 1,3-butadiene or diene mixtures, and vinyl monomers (for example styrene, acrylonitrile, vinyl chloride, vinyl acetate, vinyl alcohol, isobutylene and isoprene), such as polyhydroxy-functional acrylonitrile / butadiene copolymers, which can be prepared, for example, from epoxides or amino alcohols and carboxyl-terminated acrylonitrile / butadiene copolymers (which can be prepared, for example, as Hypro ® CTBN or CTBNX or ETBN designations are commercially available from Emerald Performance Materials); and hydrogenated polyhydroxy-functional diene polymers or copolymers.

[0056] Preferred are polyols that are liquid at room temperature.

[0057] Preference is given to polyols having an OH value of 9 to 115 mg KOH / g, preferably 14 to 60 mg KOH / g and in particular 18 to 40 mg KOH / g.

[0058] Particularly preferred are polyether polyols, dimerized or trimerized fatty acid-based polyester polyols, castor oil, castor oil derivatives or hydroxylated vegetable oils. Most preferred are polyether polyols.

[0059] Likewise suitable as compounds having two or more aldehyde groups are the reaction products of at least one polyisocyanate with at least one hydroxyaldehyde, in particular the abovementioned hydroxyaldehydes.

[0060] Suitable polyisocyanates are especially oligomeric diisocyanates, especially HDI biuret, such as Desmodur ® N 100 or N 3200 (from Covestro), Tolonate ® HDB or HDB-LV (from Vencorex) or Duranate ® 24A-100 (from Asahi Kasei); HDI isocyanurate, such as Desmodur ® N 3300, N 3600 or N 3790 BA (all from Covestro), Tolonate ® HDT, HDT-LV or HDT-LV2 (from Vencorex), Duranate ® TPA-100 or THA-100 (from Asahi Kasei) or Coronate ® HX (from Nippon Polyurethane); HDI uretdione, such as Desmodur ® N 3400 (from Covestro); HDI-iminooxadiazinedione, such as Desmodur ® XP 2410 (from Covestro); HDI-allophanates such as Desmodur ® VP LS 2102 (from Covestro); IPDI-isocyanurate, e.g. as Desmodur ® A solution of Z 4470 (from Covestro) or as Vestanat ® Solid form of T1890 / 100 (from Evonik); TDI-oligomers such as Desmodur ® II (from Covestro); or mixed isocyanurates based on TDI / HDI, such as Desmodur ® HL (from Covestro), where "HDI" stands for hexane 1,6-diisocyanate, "IPDI" stands for isophorone diisocyanate, and "TDI" stands for toluene-2,4-diisocyanate or a mixture thereof with toluene-2,6-diisocyanate. Preference is given to oligomeric diisocyanates derived from HDI, especially HDI biuret.

[0061] Preferably, polymers or polyisocyanates containing isocyanate groups and hydroxyaldehydes are reacted in an OH / NCO ratio of 1 / 1 to 1.2 / 1 at temperatures of 40 to 140° C., preferably 60 to 120° C., optionally in the presence of a suitable catalyst.

[0062] In addition to the polymers having aldehyde groups, the first component of the curable composition may contain a certain proportion of low molecular weight polyaldehydes, such as, in particular, 1,6-adipaldehyde, 1,7-heptanedialdehyde, 1,8-octanedial, 1,9-nonanedialdehyde, 2-methyl-1,8-octanedial, 1,10-decanedial, undecane-1,11-dialdehyde, dodecane-1,12-dialdehyde, hexahydro-o-phthalaldehyde, hexahydro-isophthalaldehyde, hexahydro-terephthalaldehyde, octahydro- 4,7-methylene-1H-indene dicarboxaldehyde, 3,6,9-trioxaundecane-1,11-dialdehyde, 1,3-bis(2,2-dimethyl-3-oxapropyl)imidazolidin-2-one, N,N'-bis(2,2-dimethyl-3-oxapropyl)piperazine, N,N'-bis(2,2-dimethyl-3-oxapropyl)urea, o-phthalaldehyde, isophthalaldehyde, terephthalaldehyde, 9,10-anthracene dicarboxaldehyde or naphthalene dicarboxaldehyde.

[0063] The curable composition comprises as a constituent of the second component at least one compound having two or more malonate groups of formula (I)

[0064] The compound having two or more malonate groups is preferably liquid at room temperature. In particular, its viscosity at 20° C. is 0.01-50 Pa·s, preferably 0.02-20 Pa·s, which is measured with the aid of a cone diameter of 10 mm, a cone angle of 1°, a cone tip-plate distance of 0.05 mm, a shear rate of 10 s -1 The viscosity is measured by a cone and plate viscometer of 50 mm using a cone and plate diameter of 50 mm for viscosities less than 1 Pa·s. This compound is easily processable at ambient temperature even without the addition of solvents or diluents and enables well processable compositions to be achieved.

[0065] Preferably, the average functionality of the second component relative to the malonate-containing compound is from 1.6 to 6, preferably from 1.8 to 5, especially from 2.0 to 4. This results in a cured composition having high ductility, strength and stability.

[0066] Preferably, the average molecular weight M of the second component associated with the malonate-containing compound is n The second component is 260-10000 g / mol, preferably 300-3000 g / mol. Such a second component enables a high-strength composition that is particularly easy to process.

[0067] Preferably, the compound having two or more malonate groups is obtained by reaction of at least one polyfunctional alcohol with malonic acid or at least one compound of formula (II),

[0068] Where R 1 and R 2 Each is an alkyl group having 1 to 6 carbon atoms.

[0069] Preferably, R 1 and R 2 Each is methyl, ethyl or isopropyl, especially ethyl.

[0070] Suitable polyfunctional alcohols are commercially available compounds or polymers having two or more OH groups, such as, in particular, 1,2-ethanediol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, cyclohexane-1,3-dimethanol, cyclohexane-1,4-dimethanol, diethylene glycol, dipropylene glycol, 1,1,1-trimethylolpropane, glycerol, ethoxylated or especially propoxylated glycerol, ethoxylated or especially propoxylated 1,1,1-trimethylolpropane, Alkanes, castor oil, ethoxylated or, in particular, propoxylated castor oil, ketone resin-modified castor oil, hydroxylated vegetable oils, dimerized fatty acid diols or trimerized fatty acid triols, dimerized or trimerized fatty acid-based amorphous polyester diols or triols, and the other polyols already mentioned above for the preparation of polymers containing isocyanate groups, in particular poly(oxy-1,2-propylene)diols or poly(oxy-1,2-propylene)triols or ethylene oxide-terminated poly(oxy-1,2-propylene)diols or poly(oxy-1,2-propylene)triols.

[0071] In particular, the polyfunctional alcohol is selected from 1,2-ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,6-hexanediol, cyclohexane-1,4-dimethanol, diethylene glycol, dipropylene glycol, glycerol, 1,1,1-trimethylolpropane, dimer fatty acid diol, trimer fatty acid triol, castor oil, average molecular weight M n 300 to 2000 g / mol, especially 300 to 1000 g / mol of poly(oxy-1,2-propylene) glycol and an average molecular weight M n The propoxylated 1,1,1-trimethylolpropane is 300 to 1700 g / mol.

[0072] Preferred compounds of formula (II) are dimethyl malonate, diethyl malonate, diisopropyl malonate, butyl ethyl malonate, tert-butyl ethyl malonate or di-tert-butyl malonate. Particularly preferred are dimethyl malonate, diethyl malonate or diisopropyl malonate, especially diethyl malonate.

[0073] The reaction is preferably carried out at temperatures of 50 to 150° C. with simultaneous distillative removal of liberated water or alcohol, optionally under reduced pressure and optionally in the presence of a catalyst.

[0074] In one embodiment, the reaction is carried out with at least one compound of the formula (II) and an excess of ester groups. The stoichiometry in the reaction is preferably 0.8 to 10 mol, in particular 1 to 5 mol, of compound of the formula (II) per molar equivalent of OH groups of the polyfunctional alcohol. This results in particular in a mixture of compounds having malonate groups, as shown by way of example for a difunctional alcohol in the following formula:

[0075]

[0076] wherein R is the radical of a difunctional alcohol after removal of two OH groups, x is a value from 0 or 1 to about 6, and R 1 and R 2 With the definition already given.

[0077] The higher the excess of ester groups in the reaction, the lower the average value of x. Unconverted compound of formula (II) and liberated alcohol R are preferably removed by distillation. 1 OH or R 2 OH.

[0078] In another embodiment, the reaction is preferably carried out with malonic acid and an excess of OH groups. The stoichiometry in the reaction is preferably in the range of 2.2-3.5, preferably 2.3-3.3 molar equivalents of OH groups of polyfunctional alcohols per mole of malonic acid. This forms, in particular, a mixture of compounds having malonate groups, as shown exemplarily for difunctional alcohols in the following formula:

[0079]

[0080] Here R is the radical of a difunctional alcohol after removal of two OH groups, and y is a value from 1 to about 8, in particular from 2 to 6. The lower the excess of OH groups in the reaction, the higher the average value of y.

[0081] Likewise possible are reactions in which other substances are also used.

[0082] In one embodiment of the invention, at least one further dicarboxylic acid or at least one ester of a dicarboxylic acid is additionally used in the reaction which is not malonic acid or an ester of malonic acid. This is particularly preferred in the case of reaction with an excess of OH groups. Preferred further dicarboxylic acids are adipic acid or dimer fatty acids.

[0083] Particularly preferred compounds having two or more malonate groups are 1,2-ethylene glycol bis(ethyl malonate), 1,2-propylene glycol bis(ethyl malonate), 1,3-propylene glycol bis(ethyl malonate), 1,4-butylene glycol bis(ethyl malonate), 1,6-hexanediol bis(ethyl malonate), cyclohexane-1,4-dimethanol bis(ethyl malonate), diethylene glycol bis(ethyl malonate), dipropylene glycol bis(ethyl malonate), glycerol tri(ethyl malonate), 1,1,1-trimethylolpropane-tri(ethyl malonate), dimer fatty acid diol-bis(ethyl malonate), trimer fatty acid triol-tri(ethyl malonate), castor oil-tri(ethyl malonate), 1,4-butylene glycol bis(ethyl malonate), 1,6-hexanediol bis(ethyl malonate), cyclohexane-1,4-dimethanol bis(ethyl malonate), diethylene glycol bis(ethyl malonate), dipropylene glycol bis(ethyl malonate), glycerol tri(ethyl malonate), 1,1,1-trimethylolpropane-tri(ethyl malonate), dimer fatty acid diol-bis(ethyl malonate), trimer fatty acid triol-tri(ethyl malonate), castor oil-tri(ethyl malonate), 1,4-butylene glycol bis(ethyl malonate), 1,4-butylene glycol bis(ethyl malonate), dipropylene glycol bis(ethyl malonate), 1,1,1-trimethylolpropane-tri(ethyl malonate), n Poly(oxy-1,2-propylene) glycol bis(ethyl malonate) having three ethyl malonate terminal groups and an average molecular weight M of 650 to 2500 g / mol n Propoxylated 1,1,1-trimethylolpropane, the corresponding oligomeric compounds of these reaction products, and polyester diols containing malonate groups from the reaction of diols, such as 1,6-hexanediol or cyclohexane-1,4-dimethanol, with malonic acid or diethyl malonate and optionally other dicarboxylic acids or esters thereof, such as, in particular, adipic acid or diethyl adipate or dimerized fatty acids.

[0084] Suitable compounds having two or more malonate groups are also commercially available, in particular as Acure ® 510-200 (from Allnex).

[0085] Preferably, the overall composition average functionality associated with the reactive groups aldehyde groups and malonate groups is at least 1.9, especially at least 2.0. This means that a composition having an average aldehyde functionality of, for example, 1.8 in a first component is preferably combined with a second component having an average malonate functionality of at least 2.0, preferably at least 2.1, to obtain an overall average reactive group functionality of 1.9, preferably 2.0.

[0086] The curable composition may additionally contain other ingredients, in particular the following:

[0087] - fillers, in particular ground or precipitated calcium carbonate, optionally coated with fatty acids, in particular stearates, barite, quartz powder, quartz sand, dolomite, wollastonite, kaolin, calcined kaolin, sheet silicates such as mica or talc, zeolites, aluminum hydroxide, magnesium hydroxide, silicon dioxide, including highly dispersed silicon dioxide from pyrogenic processes, industrially produced carbon black, graphite, metal powders, such as aluminum, copper, iron, silver or steel, PVC powder or hollow beads;

[0088] - fibers, in particular glass fibers, carbon fibers, metal fibers, ceramic fibers, Hanf fibers, cellulose fibers or plastic fibers such as polyamide fibers or polyethylene fibers;

[0089] – nanofillers, such as graphene or carbon nanotubes;

[0090] -dye;

[0091] – pigments, in particular titanium dioxide, chromium oxide, iron oxide or organic pigments;

[0092] – plasticizers, in particular phthalates, in particular diisononyl phthalate (DINP), diisodecyl phthalate (DIDP) or di(2-propylheptyl) phthalate (DPHP), hydrogenated phthalates, in particular diisononyl cyclohexane-1,2-dicarboxylate (DINCH), terephthalates, in particular bis(2-ethylhexyl) terephthalate or diisononyl terephthalate (DINT), hydrogenated terephthalates, in particular bis(2-ethylhexyl) cyclohexane-1,4-dicarboxylate or diisononyl cyclohexane-1,4-dicarboxylate, isophthalates, trimellitates , adipates, in particular dioctyl adipate (DOA), azelates, sebacates, benzoates, glycol ethers, glycol esters, plasticizers with a polyether structure, in particular polyoxypropylene mono-, di- or triols, or polyoxypropylene mono-, di- or triols with blocked hydroxyl groups, in particular in the form of acetate groups, and organic sulfonates or phosphates, in particular diphenylcresyl phosphate (DPK), polybutene, polyisobutene or plasticizers derived from natural fats or oils, in particular epoxidized soybean oil or linseed oil, in particular phthalates, hydrogenated phthalates, adipates or plasticizers with a polyether structure;

[0093] – solvents;

[0094] – modifiers, such as hydrocarbon resins, natural or synthetic waxes or bitumens;

[0095] - rheology modifiers, in particular urea compounds, sheet silicates such as bentonites, castor oil derivatives, hydrogenated castor oil, polyamides, polyurethanes, pyrogenic silica or hydrophobically modified polyoxyethylenes;

[0096] – Desiccants, especially molecular sieves, calcium oxide, monooxazolidines such as Incozol ® 2 (from Incorez) or orthoformate;

[0097] - adhesion promoters, in particular titanates or organoalkoxysilanes, for example aminosilanes, mercaptosilanes, epoxysilanes, vinylsilanes, (meth)acryloylsilanes, carbamatesilanes, alkylsilanes, S-(alkylcarbonyl)mercaptosilanes or oligomeric forms of these silanes;

[0098] - a catalyst, in particular a non-metallic base such as a tertiary amine, in particular 2-dimethylaminoethyl ether, 2,2'-dimorpholinodiethyl ether (DMDEE) or 1,4-diazabicyclo[2.2.2]octane (DABCO), an amidine, in particular 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 1,5-diazabicyclo[4.3.0]non-5-ene (DBN) or 1-(2-hydroxy-3-(3-trimethoxysilylpropoxy)prop-1-yl)-2-methyl-1,4,5,6-tetrahydropyrimidine, or a guanidine, in particular 1,1,3,3-tetramethylguanidine, 1-hexyl-2,3-diisopropylguanidine or 1,1'-(α,ω-polyoxypropylene)bis(2,3-diisopropylguanidine) and having an average molecular weight M n about 250-500 g / mol, and in particular basic salts such as in particular potassium acetate, potassium benzoate, potassium carbonate, potassium bicarbonate, potassium phosphate and the corresponding salts with sodium or lithium instead of potassium, wherein such basic salts are preferably used in the form of aqueous solutions, for example in a concentration of 10 to 30% by weight, based on the total weight of the solution;

[0099] - non-reactive thermoplastic polymers, such as homopolymers or copolymers of unsaturated monomers, in particular selected from ethylene, propylene, butylene, isobutylene, isoprene, vinyl acetate and alkyl (meth)acrylates, in particular polyethylene (PE), polypropylene (PP), polyisobutylene, ethylene-vinyl acetate copolymers (EVA) and atactic poly-α-olefins (APAO);

[0100] - flame-retardant substances, in particular the already mentioned aluminium hydroxide or magnesium hydroxide fillers, organic phosphates, ammonium polyphosphate, melamine or its derivatives, boron compounds or antimony compounds;

[0101] Additives, in particular wetting agents, leveling agents, defoamers, deaerators, stabilizers against oxidation, heat, light or UV radiation, or biocides;

[0102] and other materials commonly used in curable compositions.

[0103] These additives can be present as a component of the first or second component. The substances that react with 1,3-ketoester groups are preferably a component of the first component. The substances that react with aldehyde groups are preferably a component of the second component.

[0104] The curable composition preferably additionally contains at least one further ingredient selected from plasticizers, fillers and catalysts. The curable composition preferably contains several of such further ingredients.

[0105] The curable composition preferably contains at least one basic catalyst having a pKa of at least 8, preferably at least 8.5, especially an aqueous solution of a nitrogen-containing compound or a basic salt. Such compositions exhibit particularly rapid curing.

[0106] In a preferred embodiment of the invention, the curable composition contains 10-95% by weight, preferably 20-90% by weight, and in particular 30-80% by weight of filler, based on the total composition. Preference is given to fillers selected from calcium carbonate, barite, quartz powder, quartz sand, kaolin, aluminum hydroxide, titanium dioxide and carbon black. Such compositions are particularly suitable for applications with a layer thickness of at least 1 mm, preferably 1-500 mm, and in particular 1.5-250 mm. The cured composition exhibits significant elasticity.

[0107] In another preferred embodiment of the present invention, the curable composition contains 5% to 80% by weight, especially 10% to 60% by weight of a plasticizer, based on the total composition. Preferred plasticizers are selected from DINP, DIDP, DPHP, DINCH, bis(2-ethylhexyl) terephthalate, DINT, bis(2-ethylhexyl) cyclohexane-1,4-dicarboxylate, diisononyl cyclohexane-1,4-dicarboxylate, DOA, polyoxypropylene monool, polyoxypropylene diol, polyoxypropylene triol, polyoxypropylene monool-acetate, polyoxypropylene diol-diacetate, polyoxypropylene triol-triacetate and DPK.

[0108] In a particularly preferred embodiment of the present invention, the curable composition contains fillers and plasticizers; in particular, based on the total composition, 20% to 90% by weight, especially 30% to 80% by weight of fillers and 5% to 60% by weight of plasticizers.

[0109] The curable composition preferably contains less than 10%, more preferably less than 5%, in particular less than 1% by weight of volatile organic solvents having a boiling point below 250° C. at standard pressure, based on the total composition. Such compositions lead to particularly low emission levels.

[0110] Suitable solvents are also, in particular, compounds of the formula (II), such as, in particular, diethyl malonate, which can react into the curing polymer during the curing process.

[0111] The curable composition is preferably not water-based. It preferably contains substantially no water or only a small amount of water. Such a composition cures rapidly regardless of the ambient humidity, can be used between thick layers and / or waterproof substrates, and exhibits hardly any shrinkage during curing.

[0112] Preferably, the curable composition contains less than 10% by weight, preferably less than 5% by weight, in particular less than 2% by weight, of water, based on the total composition.

[0113] The curable composition preferably does not contain compounds with aldehyde groups or malonate groups in the form of emulsions or dispersions. Therefore, the compounds with aldehyde groups or malonate groups included are preferably substantially free of ionic groups or their precursors, and substantially free of longer poly(ethylene oxide) chains such as those commonly used in surfactants. This composition has high water resistance. In particular, the aldehyde-containing compound of the first component and the malonate-containing compound of the second component each have an acid group or ionic group content less than 0.1 wt %, preferably less than 0.05 wt %, based on the aldehyde-containing compound or the malonate-containing compound. Ionic groups are especially carboxylate groups, ammonium groups or sulfonate groups.

[0114] The first component of the curable composition preferably does not contain aldimine groups or only contains less than 0.2 mol, especially less than 0.1 mol of low-content aldimine groups, relative to the malonate groups in each mole of the second component. This means that the first component is substantially free of primary amines. The primary amine groups react with the aldehyde to obtain aldimines. It is not within the scope of the present invention to convert the aldehyde groups in the first component into aldimine groups. The curable composition of the present invention is mainly cured by the reaction of the malonate groups with the free aldehyde groups.

[0115] The curable composition preferably comprises in total:

[0116] - 5 to 100% by weight, preferably 10 to 70% by weight, of the sum of compounds of the formula (I) having aldehyde groups or malonate groups,

[0117] - 0 to 50% by weight, preferably 10 to 40% by weight, of plasticizer,

[0118] - 0 to 90% by weight, preferably 20 to 80% by weight, of fillers,

[0119] – and optionally other substances,

[0120] Based on the total composition.

[0121] In the curable composition, the ratio of the number of malonate groups to the number of aldehyde groups is preferably in the range of 0.5 to 2.5, more preferably in the range of 0.8 to 2.2, in particular in the range of 1 to 2. Such a ratio enables rapid, defect-free curing to obtain a polymer with high mechanical properties having high strength, ductility and stability. Particularly surprising is the fact that the ratio can be varied within this range and a non-sticky material with good mechanical properties is always obtained. As a result, the composition is particularly robust to fluctuations in the mixing ratio of the two components during processing.

[0122] The consistency of the first and second components of the curable composition is suitable so that the components can be effectively mixed with one another by simple means under ambient conditions. For this purpose, liquid or pasty components are particularly suitable.

[0123] The first and second components of the curable composition are prepared separately from one another. The ingredients of the individual components are mixed with one another to obtain a macroscopically homogeneous material. Each component is stored in a separate container. Suitable containers are in particular barrels, containers, pails, buckets, cans, bladders, bags, tubular bags, magazines or tubes. The components are storage-stable.

[0124] For use of the curable composition, the two components and any further components present are mixed with one another shortly before or during application. The mixing ratio is selected such that the ratio of the number of malonate groups to the number of aldehyde groups is in a suitable range, in particular about 1 to 2. The mixing ratio between the first and second components, based on parts by weight, is generally in the range of about 100:1 to 1:5, in particular 50:1 to 1:2.

[0125] If the components are mixed with one another before application, it must be ensured that not too much time elapses between mixing of the components and application, since otherwise the onset of reaction and the viscosity increase associated therewith could lead to defects such as inadequate leveling or delayed or incomplete adhesion to the substrate. More particularly, the open time of the composition should not be exceeded during application.

[0126] "Open time" as used herein means the time span between mixing of the components and the conclusion of a state in which the composition is suitable for processing.

[0127] Mixing is preferably carried out at ambient temperature, in particular at a temperature of from -5 to 50°C, especially from 0 to 40°C.

[0128] As the two components are mixed, the composition begins to cure by the onset of a chemical reaction. Here, it is mainly the malonate groups that react with the aldehyde groups, resulting in the composition finally curing to obtain a solid polymer material. It can be estimated that the curing reaction will form a polymer of the formula Furthermore, it can be assumed that further malonate groups which may be present will be able to add to the C=C double bonds formed and thus increase the crosslinking density.

[0129] Curing is preferably carried out at ambient temperature, in particular at a temperature of from -5 to 50°C, especially from 0 to 40°C.

[0130] The invention also provides a cured composition obtained from the curable composition after mixing of the two components.

[0131] The cured composition is preferably elastic and has high strength and ductility.

[0132] For this purpose, the cured composition preferably has a tensile strength of at least 1 MPa, preferably at least 1.5 MPa, in particular at least 2 MPa, determined in accordance with DIN EN 53504 as described in the examples.

[0133] The cured composition preferably has an elongation at break of at least 50%, preferably at least 75%, more preferably at least 100%, particularly preferably at least 150%, in particular at least 200%, determined in accordance with DIN EN 53504 as described in the examples.

[0134] The cured composition preferably has a Shore A hardness of 10 to 90, in particular 20 to 80, determined in accordance with DIN 53505 as described in the examples.

[0135] In addition, the cured composition has good heat resistance and water resistance. The cured composition preferably has high strength, ductility and hardness even after storage at 100° C. or 70° C. and 100% relative humidity for 7 days.

[0136] The curable composition is suitable for various applications, in particular as an adhesive, sealant, coating, casting resin or putty material.

[0137] The invention further provides for the use of a curable composition as an elastic adhesive, elastic sealant or elastic coating, wherein the first and second and optionally further components are mixed with one another and the mixed composition is applied in liquid form to at least one substrate.

[0138] In the case of use as elastic adhesive, elastic sealant or elastic coating, the layer thickness of the cured composition is preferably at least 1 mm, preferably 1 to 50 mm, in particular 1.5 to 25 mm.

[0139] Suitable substrates are in particular:

[0140] – glass, glass ceramics, concrete, mortar, cement mortar, fibre cement, bricks, tiles, plaster or natural rock such as granite or marble;

[0141] – Repair or levelling materials based on PCC (polymer modified cement mortar) or ECC (epoxy modified cement mortar);

[0142] – metals or alloys such as aluminium, iron, steel, copper, other non-ferrous metals, including metals or alloys with surface finishing such as zinc or chromium plating;

[0143] – bitumen or asphalt;

[0144] – leather, textiles, paper, wood, wooden materials bonded with resins (e.g. phenolic resins, melamine resins or epoxy resins), resin-textile composites or other so-called polymer composites;

[0145] – plastics, such as hard and soft PVC, polycarbonate, polystyrene, polyester, polyamide, PMMA, ABS, SAN, epoxy resins, phenolic resins, PUR, POM, TPO, PE, PP, EPM or EPDM, each of which is untreated or surface-treated, for example by plasma, corona or flame treatment;

[0146] – Fiber-reinforced plastics, such as carbon fiber-reinforced plastics (CFK), glass fiber-reinforced plastics (GFK), natural fiber-reinforced plastics (NFK) and sheet molding compounds (SMC);

[0147] – insulating foams, in particular made of EPS, XPS, PUR, PIR, rock wool, glass wool, aerogel or foamed glass (foamed glass);

[0148] – coated or painted substrates, in particular painted tiles, coated concrete, powder-coated metals or alloys or painted metal sheets;

[0149] – Paint, varnish or varnish.

[0150] If desired, the substrate can be pretreated before application, in particular by physical and / or chemical cleaning methods or by application of activators or primers.

[0151] Two identical or two different substrates may be bonded and / or sealed.

[0152] An article is obtained by using the curable composition. The article has in particular been bonded, sealed or coated with the composition. The article may be a building structure or a part thereof, in particular a building, a bridge, a roof, a staircase or a facade of an above-ground or underground building, or it may be an industrial or consumer article, in particular a window, a pipe, a rotor blade for a wind turbine, a household appliance or a means of transport, such as in particular a car, a bus, a truck, a rail vehicle, a ship, an aircraft or a helicopter, or a mounted part thereof. Example

[0153] In the following, working examples are introduced which are intended to further illustrate the invention described. It is obvious that the invention is not limited to these described working examples.

[0154] “Standard climatic conditions” (“NK”) mean a temperature of 23±1°C and a relative humidity of 50%±5%.

[0155] Unless otherwise stated, chemicals used were from Sigma-Aldrich Chemie GmbH.

[0156] Description of the measurement method:

[0157] The viscometer was set to Rheotec RC 30 cone and plate viscometer (cone diameter 10 mm, cone angle 1°, cone tip-plate distance 0.05 mm, shear rate 10 s -1 ) The viscosity is measured on a cone with a diameter of 50 mm. Viscosities less than 1 Pa·s are measured using a cone with a diameter of 50 mm.

[0158] Infrared spectra (FT-IR) were measured in the form of undiluted films on a Nicolet IS5 FT-IR instrument from Thermo Scientific equipped with a horizontal ATR measurement cell with a diamond crystal. The absorption bands are reported in wavenumbers (cm -1 )Report.

[0159] Preparation of polymers containing isocyanate groups:

[0160] Polymer P-1:

[0161] 780 g of ethylene oxide-terminated polyoxypropylene triol (Desmophen ®2.3, from Covestro) and 303 g of isophorone diisocyanate (Vestanat® IPDI, from Evonik) were converted at 80° C. by a known method into a reaction mixture having an NCO content of 9.1% by weight. Subsequently, the volatile constituents, in particular unconverted isophorone diisocyanate, were removed by distillation in a short-path evaporator (jacket temperature 160° C., pressure 0.1 to 0.005 mbar) to give a polymer having an NCO content of 1.84% by weight and a content of monomeric isophorone diisocyanate of 0.02% by weight.

[0162] Preparation of compounds having two or more aldehyde groups:

[0163] Compound A-1:

[0164] 500.0 g of the isocyanate-containing polymer P-1 were reacted with 27.7 g of 5-hydroxymethylfurfural in the presence of 0.1 g of dibutyltin dilaurate at 110° C. with removal of water until no isocyanate groups were detected by IR spectroscopy. A clear, colorless liquid was obtained with a viscosity of 63.7 Pa·s at 20° C., an average aldehyde functionality of 2.3, and a calculated aldehyde equivalent of 2381 g / eq.

[0165] The average molecular weight M of compound A-1 n In addition, the average molecular weight M was determined by gel permeation chromatography (GPC) using polystyrene (474-2520000 g / mol) as the standard, tetrahydrofuran as the mobile phase and a refractive index detector. n It is 6100g / mol.

[0166] Preparation of compounds having two or more malonate groups:

[0167] Compounds M-1 to M-6:

[0168] For each compound, the corresponding polyfunctional alcohol in the amount specified in Table 1 (in parts by weight) was mixed with the amount specified (in parts by weight) of diethyl malonate and 0.1 wt % of tetra-n-butyl titanate (Tyzor ® TnBT from Dorf Ketal) and the mixture was reacted at 140° C. under reduced pressure with removal of volatile constituents. A clear, colorless liquid was obtained in each case.

[0169] Production of curable compositions Examples Z-1 to Z-8

[0170] For each example, the ingredients of the first component (K1) specified in Table 2 were mixed with one another in the specified amounts (in parts by weight) by means of a centrifugal mixer (SpeedMixer™ DAC 150, Flacktek Inc.) and stored in a closed container.

[0171] The ingredients of the second component (K2) specified in Table 2 were processed and stored in the same way.

[0172] The "precipitated CaCO3" used is Socal ® U1S2 (from Imerys), a precipitated and stearate-coated calcium carbonate.

[0173] The "carbon black" used is Monarch ® 570 (from Cabot).

[0174] Subsequently, the two components of each composition were processed with the aid of a centrifugal mixer to obtain a homogeneous paste, which was tested as described below.

[0175] The gel time is determined by stirring a freshly mixed amount of about 3 g with a spatula at regular intervals under standard climatic conditions until stirring is no longer possible due to gelling of the mass.

[0176] The mechanical properties were determined by applying the mixed composition to a silicone-coated release paper to give a film with a thickness of 2 mm, allowing the film to cure under standard climatic conditions for 7 days, punching out several dumbbell-shaped test specimens with a length of 75 mm, a beam length of 30 mm and a beam width of 4 mm, and testing these test specimens at a tensile rate of 200 mm / min for tensile strength, elongation at break and 5% modulus of elasticity (at an elongation of 0.5%-5%) and 50% modulus of elasticity (at an elongation of 0.5%-50%) according to DIN EN 53504. In addition, several test specimens were punched out to determine the tear strength and tested at a tensile rate of 500 mm / min according to DIN ISO 34-1, method B (angular test specimens).

[0177] The Shore A hardness is determined in accordance with DIN 53505 on specimens cured under standard climatic conditions for 7 days. These results are given with the addition "7dNK". To determine the heat and water resistance, further Shore A specimens are cured under standard climatic conditions for 7 days and either stored in a forced-air oven at 100°C for 7 days or else stored at 70°C and 100% relative humidity for 7 days and the Shore A hardness stated in each case is determined after they have cooled to room temperature. These results are given as "+7 d 100°C" or "+7 d 70 / 100".

[0178] In each case, curing of the inventive examples resulted in a non-tacky, elastomeric material.

[0179] The results are reported in Table 2.

Claims

1. A curable composition comprising: - a first component containing an aldehyde group-containing compound, which comprises at least one compound having two or more aldehyde groups, and - a second component containing a malonate group-containing compound, which comprises at least one compound having two or more malonate groups of formula (I) The average molecular weight M of at least one of the two components related to the compound containing aldehyde groups or malonate groups is n In the range of 400 to 20000 g / mol.

2. The composition according to claim 1, characterized in that The compound having two or more aldehyde groups is liquid at room temperature, and in particular has a viscosity at 20° C. of 0.2-700 Pa·s, preferably 0.3-500 Pa·s, more preferably 0.5-200 Pa·s, which is measured by a cone diameter of 10 mm, a cone angle of 1°, a cone tip-plate distance of 0.05 mm, a shear rate of 10 s -1 The viscosities were measured with a cone and plate viscometer and for viscosities less than 1 Pa·s a cone diameter of 50 mm was used.

3. The composition according to any one of claims 1 or 2, characterized in that The average molecular weight M of the first component related to the aldehyde-containing compound n In the range of 1000 g / mol to 20000 g / mol, preferably 1500 g / mol to 15000 g / mol, in particular 2000 g / mol to 10000 g / mol, it is measured by means of gel permeation chromatography (GPC) relative to polystyrene as standard.

4. The composition according to any one of claims 1 to 3, characterized in that The aldehyde group-containing compound comprises a polymer having a polymer backbone comprising a poly(oxyalkylene) unit and / or a polyester unit.

5. The composition according to any one of claims 1 to 4, characterized in that The aldehyde-containing compound comprises a polymer containing urethane groups, which is liquid at room temperature and has an average molecular weight M of 1000 g / mol to 20000 g / mol, preferably 1500 g / mol to 15000 g / mol, in particular 2000 g / mol to 10000 g / mol. n and an average aldehyde functionality of 1.8 to 3.5, preferably 2.0 to 3.0, especially 2.2 to 3.

0.

6. The composition according to any one of claims 1 to 5, characterized in that The compounds having two or more aldehyde groups are obtained from the reaction of at least one hydroxyaldehyde with at least one polymer containing isocyanate groups or at least one polyisocyanate.

7. The composition according to any one of claims 1 to 6, characterized in that The compound having two or more malonate groups is liquid at room temperature.

8. The composition according to any one of claims 1 to 7, characterized in that The average functionality of the second component relative to the compound containing malonate groups is from 1.6 to 6, preferably from 1.8 to 5, in particular from 2.0 to 4.

9. The composition according to any one of claims 1 to 8, characterized in that The compound having two or more malonate groups is obtained by reacting at least one polyfunctional alcohol with malonic acid or at least one compound of formula (II) Where R 1 and R 2 Each is an alkyl group having 1 to 6 carbon atoms, preferably a methyl group, an ethyl group or an isopropyl group, in particular an ethyl group.

10. The composition according to any one of claims 1 to 9, characterized in that Based on the total composition, the filler is contained in an amount of 10% to 95% by weight, preferably 20% to 90% by weight, in particular 30% to 80% by weight.

11. The composition according to any one of claims 1 to 10, characterized in that Based on the total composition, 5 to 80% by weight, in particular 10 to 60% by weight, of plasticizer is contained.

12. The composition according to any one of claims 1 to 11, characterized in that Based on the total composition, less than 10% by weight, preferably less than 5% by weight, in particular less than 1% by weight, of volatile organic solvents having a boiling point of less than 250° C. at standard pressure are contained.

13. A cured composition obtained from a curable composition according to any one of claims 1 to 12 after mixing two components, wherein the cured composition has in particular a tensile strength of at least 1 MPa, preferably at least 1.5 MPa, in particular at least 2 MPa, and / or an elongation at break of at least 75%, preferably at least 100%, in particular at least 150%, measured at a tensile rate of 200 mm / min on a dumbbell-shaped test piece with a thickness of 2 mm, a length of 75 mm, a beam length of 30 mm, and a beam width of 4 mm according to DIN EN 53504.

14. Use of the composition according to any one of claims 1 to 13 as an elastic adhesive, elastic sealant or elastic coating, wherein the first component and the second component and optionally other components are mixed with one another and the mixed composition is applied in liquid form to at least one substrate.

15. The method according to claim 14, wherein the cured composition has a layer thickness of at least 1 mm, preferably 1 to 50 mm, in particular 1.5 to 25 mm.

Citation Information

Patent Citations

  • Composition crosslinkable by Real Michael Addition (RMA) reaction

    US20180282477A1